1995
DOI: 10.1038/sc.1995.98
|View full text |Cite|
|
Sign up to set email alerts
|

Superoxide radicals play important roles in the pathogenesis of spinal cord injury

Abstract: To investigate a possible role of supreoxide dismutase (SOD) in the pathogenesis of spinal cord injury (SCI), the change in the circulatory status in an experimental SCI model of rats was examined. The blood pressure (BP) of the SCI group decreased markedly by compression or head-up-tilt (60°). The extent of the BP decrease was diminished by the administration of a long acting SOD (SM-SOD) prior to injury. Compression, tilting and the administration of SM-SOD increased the sensitivity of resistant arteries to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 19 publications
0
24
0
Order By: Relevance
“…15 However, Nishibe showed that SOD activity is generally much lower than that of CAT activity in spinal cord tissues. 40 Therefore, SOD activity changes observed due to melatonin treatment are less pronounced than those seen in CAT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…15 However, Nishibe showed that SOD activity is generally much lower than that of CAT activity in spinal cord tissues. 40 Therefore, SOD activity changes observed due to melatonin treatment are less pronounced than those seen in CAT.…”
Section: Discussionmentioning
confidence: 99%
“…11,18,[26][27][28][29][30] Free oxygen radicals can impair the function of the cellular components. 14,15,31 Free oxygen radical-induced damage has been implemented in postischemic cell injury and cell death, while free radical scavengers such as SOD, CAT and GSH-Px are associated with partial amelioration of ischemic injury. 4,5 The extent of lipid peroxidation is a useful parameter for evaluating cellular disturbances caused by spinal cord trauma under experimental conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7] Previous studies have demonstrated that the formation of ROS including hydroxyl radical, superoxide and hydrogen peroxide immediately after central nervous system injury may contribute to the pathogenesis of SCI. 8,9 Source of ROS. Production of ROS under physiological conditions is important for normal cellular redox reactions.…”
Section: Ros and Oxidative Stress In Scimentioning
confidence: 99%
“…NRF2 promotes neuronal survival in neurodegeneration and acute nerve damage been observed in such conditions, and thus antioxidation strategies may prove beneficial for these cases as well (33)(34)(35). Whereas photoreceptor cells are highly specialized and unusual neurons, retinal ganglion cells (RGCs) are more typical of the types of CNS projection neurons that suffer damage in acute crush injuries.…”
Section: Introductionmentioning
confidence: 99%